Numerical simulations of flow-induced vibrations of two rigidly coupled cylinders with uneven diameters in the upper transition Reynolds number regime. (August 2021) - Pires Vieira Serta, Clarissa; Janocha, Marek Jan; Yin, Guang; Ong, Muk Chen
Abstract: Two degree-of-freedom (2-DoF) flow-induced vibrations (FIV) of two rigidly coupled cylinders are numerically investigated at the Reynolds number of 3 . 6 × 1 0 6 . Two-dimensional (2D) Unsteady Reynolds-Averaged Navier–Stokes (URANS) simulations are performed combined with the k − ω SST turbulence model. A low mass-damping system is considered with a mass ratio of 2 and a damping ratio of zero. The diameter ratio is set to 0.25. The influence of the reduced velocity ( U r ), the position angle ( α ) of the small cylinder relative to the large cylinder and the gap ratio ( G / D ) between the cylinders on the FIV response of the system are analyzed. The simulations are performed for 2 ≤ U r ≤ 12 . To analyze the effect of α, three values are considered, [ α = 0 °, 90 °, 180 ° ] with a constant value of G / D = 0 . 1 . The effect of G / D is studied for the α = 90 ° configuration in which the G / D = 0 . 25 and G / D = 0 . 5 configurations are analyzed in addition to the G / D = 0 . 1 configuration. It is found that the lock-in regime extends beyond U r = 12 for the α = 0 °, 180 ° and α = 90 ° at G / D = 0 . 1 and 0.25 configurations compared with the single cylinder configuration. Extended lock-in range is observed when the small cylinder is placed at α = 90 °, with G / D = 0 . 1, and at α = 180 ° . In addition, for the α = 90 ° configuration, the results obtained for C ¯ D, C ¯ L and A y, m a x / D converge to those of the single cylinder with the increase of G / D . A 2T shedding mode is observed for the single cylinder at 6 . 5 ≤ U r ≤ 10 and for the α = 0 ° configuration when U r ≥ 8 . For the α = 90 ° and 180 ° configurations, the wake patterns are irregular. With the increase of G / D, a longer vortex street behind the small cylinder is observed, which creates many vortical structures in the wake of the cylinders. Highlights: Flow-Induced Vibrations of two rigidly coupled cylinders with uneven diameters are investigated. 2D URANS simulations are performed at Re = 3 . 6 × 1 0 6 . An extended lock-in range is observed for the α = 90 ∘ and 180 ∘ configurations. For large gap between cylinders the vibration response of cylinders bundle is similar to that of a single cylinder. Regular vortex shedding appears when α = 0 ∘ at high reduced velocities and irregular wake patterns appears when α = 90 ∘ and 180 ∘ .